STATE RESPONSIBILITY AND CONSTITUTIONAL PROTECTION OF PERSONAL DATA IN INDONESIA: ADDRESSING DIGITAL CHALLENGES - Wa Ode Reni; Syahbudin; Abdul Halim Momo (Universitas Syiah Kuala, 2025)
The rapid expansion of Indonesia’s digital ecosystem has intensified internet usage across public services, commerce, and governance, yet it has also exposed the country to critical risks of personal data misuse. Indonesia remains particularly vulnerable due to uneven cybersecurity capacity, fragmented data governance, and limited enforcement of existing regulations. These weaknesses amplify the potential for cross-border data breaches and undermine public trust in state institutions. This study analyzes personal data protection as a constitutional right and evaluates the Indonesian state’s responsibility to safeguard this right amid growing digital challenges. Employing a normative legal method with statutory, conceptual, and comparative approaches, the research reveals that while Indonesia’s constitutional and statutory frameworks, anchored in Pancasila, Article 28G(1) of the 1945 Constitution, and the 2022 Personal Data Protection Law, form a strong normative basis, their practical implementation remains inconsistent. Comparative analysis with jurisdictions such as the European Union and South Korea highlights Indonesia’s institutional weaknesses, particularly in regulatory coordination, public awareness, and sanction mechanisms. This study recommends adopting explicit safeguards inspired by the EU General Data Protection Regulation (GDPR), such as stricter breach-notification duties, independent supervisory authority, and mandatory data-protection impact assessments, while strengthening Indonesia’s digital infrastructure and enforcement mechanisms to ensure the state’s constitutional responsibility for personal data protection is effectively fulfilled in the digital era.